Academic literacy and the decontextualised learner - Boughey, Chrissie; McKenna, Sioux (Critical Studies in Teaching and Learning, 2023)
The  literacy  practices that  are  valued  in the  university emerge  from specific  disciplinary histories  yet  students  are  often  expected  to  master  these  as  if  they  were  common  sense  and natural. This article argues that the autonomous model of literacy, which sees language use as the application of a set of neutral skills, continues to dominate in South African universities. This model denies the extent to which taking on disciplinary literacy practices can be difficult and have implications for identity. It also allows disciplinary norms to remain largely opaque and beyond critique. Furthermore, the autonomous model of literacy is often coupled with a discourse  of  the  ‘decontextualised  learner’  who  is  divorced  from  her  social  context,  with higher  education  success  seen  to  be  resting  largely  upon  attributes  inherent  in,  or  lacking from,  the  individual.  Sadly,  alternative  critical  social understandings  have  not  been  widely taken  up  despite  their  being  well  researched.  Indeed,  such  understandings  have  often  been misappropriated  in  ways  that  draw  on  critical  social  terminology  to  offer  autonomous, decontextualised, remedial student interventions. We argue that these issues are implicated in students’ accusations that universities are alienating spaces.